Wuthering Heights - Wasowski, Richard (New York Wiley, 2001)
The original CliffsNotes study guides offer expert commentary on major themes, plots, characters, literary devices, and historical background. The latest generation of titles in this series also feature glossaries and visual elements that complement the classic, familiar format. In CliffsNotes on Wuthering Heights, you explore one of Emily Bront? most beloved and enduring novels, combining realism and gothic symbolism to tell a love story that's full of social relevance. In the novel, you follow the self-destructive journey of Heathcliff, as he seeks his revenge for losing his childhood love, Catherine, to another man. This study guide carries you through Heathcliff's life by providing summaries and commentaries on each chapter of the novel. Critical essays give you insight into the narrative structure of the novel, the major themes Bront? explores, and Heathcliff's obsession. Other features that help you study include Character analyses of the main characters A character map that graphically illustrates the relationships among the characters A section on the life and background of Emily Bront? A review section that tests your knowledge A Resource Center full of books, articles, films, and Internet sites Classic literature or modern modern-day treasure -- you'll understand it all with expert information and insight from CliffsNotes study guides
Includes bibliographical references (p. [82]-83) and index.
115567
Keywords: Bronte, Emily -- 1818-1848. -- Examinations -- Study guides; Wuthering Heights (Bronte, Emily); 1800-1899; American fiction -- 19th century -- Study guides; American fiction; Examinations; Study guides